PENGARUH AROMATHERAPY LEMON TERHADAP MUAL PADA IBU HAMIL SYSTEMATIC LITERATURE REVIEW - Thalia Safira; Yocki Yuanti; Lisa Trina Arlym (JURNAL KESEHATAN INDRA HUSADA, 2022)
Nausea and vomiting usually begins in the 6th week of pregnancy which is called “morning sickness” because it occurs in the morning. Lemon aromatherapy is one of the aromatherapy with the main content of limonene which can reduce nausea. The purpose of this study was to examine several journals related to the effect of lemon aromatherapy on nausea in pregnant women. This type of research is Systematic Literature Review by searching for journals using Google Scholar, ProQuest, PubMed, and GARUDA databases from 2017-2022 and the literature selection process using PRISMA diagrams. Based on the search results, it was found that seven articles experienced a decrease in the lowest nausea and vomiting by 2 scores and the most decreased by 7 scores. The conclusion of this study is that lemon aromatherapy has an effect on reducing nausea in first trimester pregnant women, which is carried out at least once a day for a week for a duration of 5 minutes.